ENTREPRENEURIAL CAPABILITIES IN THELITERATURE FROM 2020 TO 2024 - Maria del Rosario Molina Gonzalez (IPHO-Journal of Advance Research in Science And Engineering, 2024)
Entrepreneurial skills are the result of the establishment offreedoms and opportunities, while they are antecedents of social responsibility. Thus, the purpose of writing this was defined as a model for the study of entrepreneurial skills in situations of scarcity of resources and political corruption. For this purpose, we carried out a documentary study indexed and recorded with ISSN and DOI during the period from 2020 to 2024. Later sources, the information was processed into arrays of content analysis to establish the central themes of the agenda research and to build a model of observable to specify the study of social entrepreneurship variables. Under the state of knowledge warns of the emergence of approaches ranging responsibilities capabilities, a discussion was made by comparing the analysis of the literaturein question.